Lectotypification of four names in the genus Gymnosporia (Celastraceae) - Bhat, Abhishek T.; Prabhukumar, Konickal Mambetta; Rana, Tikam Singh (Phytotaxa, 2024)
While revising the genus Gymnosporia with respect to India, it was found that four names viz. G. emarginata, G. rufa, G. rufa var. latifolia and G. wallichiana required lectotypification and are typified here as per the recent rules of ICN.